The Impact of Trade Liberalization on Household Welfare in Vietnam - Seshan, Ganesh (World Bank, Washington, DC, 2012)
What is the effect of trade liberalization on households in developing countries? To what extent do the poor benefit when local markets are made more accommodative to international trade? The author empirically analyzes the distributional impact of trade policies on households in a low-income country with a large rural economy where labor markets are imperfect. The methodology in this paper, which can be applied to various types of labor market conditions, relates changes in prices attributed to trade reforms to changes in household welfare, income distribution, and poverty using theoretically consistent measures of producer and consumer welfare. The author investigates the effects on poverty and income distribution of national and international market integration in Vietnam's rice sector and fertilizer market between 1993 and 1998, a period of ongoing market reforms when the national poverty rate fell sharply from 59 percent to 37 percent. He finds that when the effects of opening the rice and fertilizer market are isolated, Vietnam's agricultural trade reforms did not contribute to a significant improvement in overall household welfare or decline in poverty over this period. Nonetheless, the liberalization exercise can explain about half of the reduction in poverty incidence among farm households. The results also show that liberalization did not exacerbate income inequality, but did generate gains for rural households across the distribution, particularly the poor, at the expense of urban households.